Selection of orphan Rhs toxin expression in evolved Salmonella enterica serovar Typhimurium. - Sanna Koskiniemi; Fernando Garza-Sánchez; Linus Sandegren; Julia S Webb; Bruce A Braaten; Stephen J Poole; Dan I Andersson; Christopher S Hayes; David A Low (PLoS Genetics)
Clonally derived bacterial populations exhibit significant genotypic and phenotypic diversity that contribute to fitness in rapidly changing environments. Here, we show that serial passage of Salmonella enterica serovar Typhimurium LT2 (StLT2) in broth, or within a mouse host, results in selection of an evolved population that inhibits the growth of ancestral cells by direct contact. Cells within each evolved population gain the ability to express and deploy a cryptic "orphan" toxin encoded within the rearrangement hotspot (rhs) locus. The Rhs orphan toxin is encoded by a gene fragment located downstream of the "main" rhs gene in the ancestral strain StLT2. The Rhs orphan coding sequence is linked to an immunity gene, which encodes an immunity protein that specifically blocks Rhs orphan toxin activity. Expression of the Rhs orphan immunity protein protects ancestral cells from the evolved lineages, indicating that orphan toxin activity is responsible for the observed growth inhibition. Because the Rhs orphan toxin is encoded by a fragmented reading frame, it lacks translation initiation and protein export signals. We provide evidence that evolved cells undergo recombination between the main rhs gene and the rhs orphan toxin gene fragment, yielding a fusion that enables expression and delivery of the orphan toxin. In this manner, rhs locus rearrangement provides a selective advantage to a subpopulation of cells. These observations suggest that rhs genes play important roles in intra-species competition and bacterial evolution.